Liriomyza cyclaminis a new species leaf miner of Cyclamen (Bollettino di zoologia agraria e bachicoltura, 2024)
Liriomyza cyclaminis, a new species of Agromyzidae, leaf miner of Cyclamen hederifolium and C. repandum is described.The male genitalia place cyclaminis in the equiseti group and are very similar to those of virgula, but there is no evidence as to the host-plant.